Design Jigsaw: Exploring a Computational Approach to Assembling Ideas in the Design Production Process. (June 2014) - Lo, Chia-Hui Nico; Lai, Ih-Cheng; Chang, Teng-Wen
Idea generation in the design production process often occurs within brainstorming sessions. Linking ideas is the key mechanism in the process of producing design. Through linking ideas, a graph-like knowledge is achieved in representing the individual memories, with the nodes and arcs being the ideas and the links between ideas respectively. The design process is similar to doing a jigsaw. Using the jigsaw metaphor, a cognitive study is applied to the design tool DIM (Dynamic Idea Map) to explore computational jigsaw mechanisms. Thereafter, a computational framework called Design Jigsaw is developed to support students in assembling vast ideas effectively and reveals the construction of meaning in the graph-like knowledge structure of design thinking